Infectious Complications of Central Venous Catheterization - E. Yu. Matveyeva; A. V. Vlasenko; V. N. Yakovlev; V. G. Alekseyev (Общая реаниматология, 2011)
The extensive introduction of invasive diagnosis and treatment methods into medical practice is inseparably linked with the necessity of catheterizing the vessels to monitor patient status and to administer medications and other agents into the vascular bed. This results in increased number of cases of catheter-related blood stream infections, which are more than 60% of hospital-acquired bacteremias and 11—37% of all nosocomial infections in Europe. The association of sepsis with an infected catheter is 20—29 to 55%. No specific clinical manifestations of catheter septicemia (and hence its late diagnosis and delayed treatment) and difficulties in identifying a venous catheter as a source of a septic process make it necessary to pay particular attention to the prevention of infectious complications both when placing a central venous catheter and when applying a venous access. Various preventive measures have been developed to reduce the incidence of infections. The measures decreasing catheter-site or infusion system colonization are most effective. Key words: puncture, catheterization, venous access, central venous catheter, colonization, infection, nosocomial infections, catheter-related blood stream infections, septicemia, catheter sepsis.